Physical and chemical characteristics of the sediment in the estuarine region of Cananeia (SP), Brazil - Jorcin, A. (Kluwer Academic Publ, 2000)
Physical and chemical characteristics of sediment were analyzed at eight sampling areas in the estuarine region of Cananeia (SP), Brazil. The samples were collected in 1995 during four periods; summer, autumn, winter and spring. Total nitrogen and phosphorus concentrations, redox potential, water and organic matter percentage, sand and silt percentage and grain size were determined in six different layers of 20 cm deep columns of sediment. In general, the nutrient concentration and the percentage of organic matter decreased with depth and greater variations were observed in the first centimeter of the samples. Differences in nutrient concentration and organic matter were also observed during the study period. The highest concentrations were recorded during the rainy season (February) as a consequence of an accumulation of organic matter brought into the system by rivers and adjacent flooded areas. In general, the sediments had oxidized characteristics until the 5 or 10 cm depth in areas near the rich coastal vegetation. However, in areas open to the ocean, the entire sediment columns were almost completely oxidized.
Keywords: sediments; vertical distribution; nutrient; redox potential; estuarine ecosystem